1970
DOI: 10.1017/s0022112070000058
|View full text |Cite
|
Sign up to set email alerts
|

Reflexion of an oblique shock wave by a turbulent boundary layer

Abstract: Measurements are presented of the reflected wave field produced by a plane oblique shock wave impinging on a turbulent boundary layer at an initial Mach number of 2·5. The outgoing waves are either a single shock, with the same deflexion as the incident shock, or a shock of approximately 10° deflexion followed by a region of compression in which is embedded an expansion fan having the same turning as the incident shock. The transition between these two types of wave field was not studied, but it is fairly abru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 2 publications
(3 reference statements)
1
13
0
Order By: Relevance
“…It is notable that, within the limits of accuracy of the measurements, the time-averaged shock angle β 02 and, hence, deflection across the separation shock ϑ 02 remain constant for the cases SWBLI 2-5 ( β 02 ≈ 41 • ). A similar observation was made by Green (1970), who stated that once separation has occurred, the shock strength of the separation shock C 2 is independent of the incident shock that causes separation. This behaviour is characteristic for a free interaction (Chapman et al 1958), meaning that the pressure rise towards separation depends neither on the source of separation, in particular the shock intensity, nor on the downstream geometry (Delery & Dussauge 2009).…”
Section: Numerical Results For Machsupporting
confidence: 74%
See 2 more Smart Citations
“…It is notable that, within the limits of accuracy of the measurements, the time-averaged shock angle β 02 and, hence, deflection across the separation shock ϑ 02 remain constant for the cases SWBLI 2-5 ( β 02 ≈ 41 • ). A similar observation was made by Green (1970), who stated that once separation has occurred, the shock strength of the separation shock C 2 is independent of the incident shock that causes separation. This behaviour is characteristic for a free interaction (Chapman et al 1958), meaning that the pressure rise towards separation depends neither on the source of separation, in particular the shock intensity, nor on the downstream geometry (Delery & Dussauge 2009).…”
Section: Numerical Results For Machsupporting
confidence: 74%
“…Green 1970;Delery & Marvin 1986), we applied the free interaction theory to carefully analyse our numerical results. We found that only the generalised form of the free interaction theory (Carrière et al 1969) correlates the wall-pressure rise towards separation for different Mach and Reynolds numbers.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then shock C2 intersects the oblique shock C1 at point H, from which emanate the two refracted shocks C3 and C4. The point H could be seen clearly in the Schlieren pictures [2] at deflection angles of 6. For the accuracy of numerical results, the treatment of the sublayer, which is very close to the solid wall, plays an important role, since molecular diffusion results in the significant transport of heat and momentum.…”
Section: Introductionmentioning
confidence: 84%
“…1 left), the boundary layer remains attached, and the interaction is embedded well in the boundary layer. Green [2] studied cases at Mach 2.5, Re θ of 4×10 5 , deflection angles of 2 o , 2.5 o and 5 o and showed that the reflected wave is a single shock with equal and opposite reflection angle to that of the incident wave. For stronger interactions (see Fig.…”
Section: Introductionmentioning
confidence: 99%